Apparent Life-Threatening Events in Neonatal Period: Clinical Manifestations and Diagnostic Challenges in a Pediatric Referral Center - Kadivar, Maliheh (Tehran University of Medical Sciences, 2013)
OBJECTIVE: Apparent Life-Threatening Events (ALTEs) is an episode that is frightening to the observer and is characterized by some combination of apnea, color change, altered muscle tone, choking, and gagging. This study was designed to evaluate and follow up neonates who presented with clinical manifestation of an ALTE in a year. METHODS: In this prospective observational study, all of the neonates with episode of ALTE who were admitted to the Children's Medical Center (CMC) in Tehran, from June 15(th) 2010 to May 14(th) 2011 were enrolled in the study. Data from patients consisting of history, physical examinations, and paraclinical findings were recorded in a checklist and all followed up 3 to 6 months after discharge. FINDINGS: During the study period 18 neonates were admitted due to ALTE episode(s) with mean age of 15±13 days. Nine (50%) neonates had previous attacks of ALTE. The most frequent complaint was cyanosis in 12 (67%) and apnea in 8 (44%) patients. In 10 (56%) the event lasted less than one minute, 13 (72%) were awake, 17 (95%) in supine position and 13 (72%) on their parent's lap. Primary antagonistic impression on admission was sepsis in 11 (61%) and concomitant seizure in 5 (28%). The most common final diagnosis according to repeated physical examinations, result of paraclinical investigations and follow up was sepsis 4 (22%) and aspiration 9 (50%). ALTE recurred in none of the neonates during follow up. CONCLUSION: The rate of ALTE seems to be higher than in this study owing to high incidence of recurrent ALTE. Although most of these attacks regress spontaneously, more attention should be paid for the underlying diseases.